PENDIDIKAN KEWARGANEGARAAN: URGENSI PEMILU DAN PARTAI POLITIK BAGI MASYARAKAT DESA PANTAI RAJA KABUPATEN KAMPAR - AURADIAN MARTA; Raja Muhammad Amin; Wan Asrida; Baskoro Wicaksono (Universitas Islam Raden Rahmat Malang, 2021)
Civic education aims to build and shape the character of citizens by Pancasila and the 1945 Constitution. One aspect of civic education that needs to be developed is regarding elections and politics which are fundamental elements of democratization. The targets of this activity are village government officials, village communities, and community leaders in Pantai Raja Village. This community service activity is carried out in the form of socialization politics with the stages of preparation, implementation, evaluation, and recommendations. The results of civic education in Pantai Raja Village are the results of increasing the community's ability to identify problems in elections and politics that are focused on identity politics, voter data, and black campaigning.